Impact of planting rotations and tree age on insect pests and weeds in balsa plantations of East New Britain, Papua New Guinea - MALAGAT BOAS; JOSHUA URIM; KARI SOGERA IAMBA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Boas M, Urim J, Iamba KS. 2025. Impact of planting rotations and tree age on insect pests and weeds in balsa plantations of East New Britain, Papua New Guinea. Biodiversitas 26: 1618-1629. Balsa (Ochroma pyramidale) is an income-generating tree crop in East New Britain Province (ENB) of Papua New Guinea, and repetitive planting (rotations) on the same piece of land can result in pest and weed incursions. We sampled insects and weeds from three planting rotations: rotation 1, 2, and 3, and across two age groups: 1-9 months and 10-18 months old trees within each rotation. We found that the age of trees did not strongly affect pest abundance. The reason is that most of the pests associated with balsa trees are cocoa pests and were present in the soil before the blocks were cleared for the first planting. However, the planting rotations had a strong effect, suggesting how harvesting and clearing can affect the colonization and establishment of insects. The abundance of insects increased with planting rotations, with most individuals participating in the third rotation. In contrast, the diversity of pests between young trees (1-9 months) did not differ significantly from older trees (10-18 months). Since the plantations studied are generally young (<2 years), leaves are less lignified; therefore, there is lower attractiveness and colonization by insect pests. Weed abundance was strongly associated with planting rotations and tree age. However, neither factor affected the species richness of weeds, hence the diversity. This can be explained by the exotic status of weed species and supported by the Enemy Release Hypothesis (ERH). Many weed species sampled are invasive and are free from natural enemies. We assume that high pest diversity in rotation two directly responds to the availability of natural vegetation near balsa plantations that provide refugia for insects. This study emphasizes the importance of land use history and how past host plants such as cocoa or coconut can sustain pest load and affect balsa trees. It also provides information on intercrop systems and their impact on pest and weed infestation in balsa plantations. Overall, the findings are relevant to plant protection management.